Novel Design of a Magnetically Switchable MOSFET using Magnetoresistive Elements - Chinmay Vilas Samak; Tanmay Vilas Samak (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
Various research activities have been carried out, individually, in the fields of MOSFET design andanalysis, and magnetoresistance; however, ourresearch focused on the design and analysis of a magnetically switchable MOSFET with the application of magnetoresistive elements. Theoretical study, calculations and simulations were used in order to design and analyze the magnetically switchable MOSFET. It was observed that the magnetoresistance values of 42%, 81% and 95%, respectively, for giant magnetoresistive element, tunneling magnetoresistive element and colossal magnetoresistive element resulted in reduced resistance values of 139.2Ω, 45.6Ω and 12Ω across the MOSFET in presence of magnetic field; as compared to a higher value of 240Ω in its absence. As a consequence, the gate-source voltage increased beyond the threshold value (1.5V), and the MOSFET switched ON. Accordingly, a magnetically switchable MOSFET was designed and its behavioural characteristics were analyzed.